The Role Of Core Competency Of Human Resources In Achieving Organizational Excellence: Applied Study In Public Company Of Electrical Industrial - Hasan Jumaah, Mahmood (Opción, 2019)
The current research aims to test the relationship linkage and the effect between the core competency for human resources and organizational excel- lence, the problem of the research is the role of core competency of human resources in achievement organizational excellence in the state company of electrical industry. A questionnaire was used in data collection depending on the distribution of (58) questionnaire to the research sample. Data were ana- lyzed using (SPSS) program. Using a number of statistical tools to test the re- search hypothesis. The research came out with a set of conclusions, one of the most important thinks was that there is a linkage and impact relation between core competency of human resources, it’s variables (leadership competency, intellectual competency, self-management competency, make decisions com- petency) and organizational excellence as a whole. The research came out with many suitable recommendations.